Comparative evaluation of concrete flexural strength of river bed and crusher run coarse aggregate in Pokhara valley - Katuwal, Tek Bahadur (Journal of Innovations in Engineering Education, 2019)
Concrete is fundamental construction material widely used for every building structure and other infrastructure. Aggregate has significantfunctions as concrete making materials for the solidity and strength of concrete.The objective of this research was comparative evaluation of crusher and river bed coarse aggregate in respect to the flexural strength of M20 grade concrete with nominal mix. For this research, sample were taken from Kotre Crusher(KC), Kotre River Bed (KR), Hemja Crusher (HC) and Hemja River Bed (HR) considering sand from single source and cement remains singlebrand.Nine cubes (500 mm × 100 mm×100mm) were cast for each sampled source and the flexural strength was determined using a single point load flexural testing machine after 7 days, 14 days and 28 days of curing. The mean flexural strength for the KC, KR, HC and HR sources were 4.86 N/mm2, 4.34 N/mm2, 4.58 N/mm2 and 4.1N/mm2, respectively. Also, the percentageincrement of flexural strength for KC, KR, HC and HR sources are 23.31, 19.11, 19.88 and 18.12 from 7 days to 14 days and 20.90, 16.04, 18.65 and 16.48 from 14 days to 28days respectively. Modulus of rupture of all aggregate sources are greater than theminimum flexural strength as per IS: 456 – 2000. Finally, outcomes of the study indicated that the flexural strength of Kotre Crusher aggregate is more than other sources and all selected samples applicable for construction work.